2021
DOI: 10.7150/thno.52574
|View full text |Cite
|
Sign up to set email alerts
|

Electroacupuncture ameliorates intestinal inflammation by activating α7nAChR-mediated JAK2/STAT3 signaling pathway in postoperative ileus

Abstract: Inflammatory cytokines produced by muscularis macrophages largely contribute to the pathological signs of postoperative ileus (POI). Electroacupuncture (EA) can suppress inflammation, mainly or partly via activation of vagal efferent. The goal of this study was to investigate the mechanisms by which EA stimulation at an hindlimb region ameliorates inflammation in POI. Methods: Intestinal motility and inflammation were examined after 24 h after intestinal manipulation (IM)-induced POI in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
70
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 97 publications
(79 citation statements)
references
References 40 publications
(24 reference statements)
1
70
0
Order By: Relevance
“…A recent study had accordingly revealed that EA (10 Hz, 1 mA, plus width 0.4 ms) at ST36 could reduce the production of inflammatory cytokines by activating α7nAChRmediated JAK2/STAT3 signaling pathway in macrophages, thereby suppressing gastrointestinal inflammation and promoting its motility [17], which demonstrated the antiinflammatory and analgesic effects of EA through vagus nerve from the point of view of the complete nerve circuit. Another recent study showed that EA at ST36 with low intensity (0.5 mA) can activate sensory neurons expressing PROKR2+, thus driving the vagal-adrenal axis to play a systemic anti-inflammatory effect, and pointed out that the anti-inflammatory effect of acupuncture was related to the intensity of stimulation and the depth of acupuncture [89].…”
Section: Animal Studies Acupuncture Has Been Shown To Have Several Beneficial Effects In Animals With Intestinal Disordersmentioning
confidence: 97%
See 1 more Smart Citation
“…A recent study had accordingly revealed that EA (10 Hz, 1 mA, plus width 0.4 ms) at ST36 could reduce the production of inflammatory cytokines by activating α7nAChRmediated JAK2/STAT3 signaling pathway in macrophages, thereby suppressing gastrointestinal inflammation and promoting its motility [17], which demonstrated the antiinflammatory and analgesic effects of EA through vagus nerve from the point of view of the complete nerve circuit. Another recent study showed that EA at ST36 with low intensity (0.5 mA) can activate sensory neurons expressing PROKR2+, thus driving the vagal-adrenal axis to play a systemic anti-inflammatory effect, and pointed out that the anti-inflammatory effect of acupuncture was related to the intensity of stimulation and the depth of acupuncture [89].…”
Section: Animal Studies Acupuncture Has Been Shown To Have Several Beneficial Effects In Animals With Intestinal Disordersmentioning
confidence: 97%
“…is alternative medicine has also demonstrated promising anti-inflammatory effects; therefore, it has been applied to treat inflammatory diseases [16][17][18], especially inflammatory pain [19][20][21][22]. Numerous studies have so far elucidated the underlying mechanism of acupuncture for various types of pain, including visceral pain [22,23], and it has been emphasized that anti-inflammatory effects can contribute to the analgesic mechanism of this alternative therapy.…”
Section: Introductionmentioning
confidence: 99%
“…In OA models, EA at Ex-LE4 ( Neixiyan ) and ST35 ( Dubi ) can significantly inhibit the activation of the NLRP3 inflammasome and the protein expression of matrix metalloproteinase-13, caspase-1, and IL-1β in cartilage tissue, thereby reducing mechanical hyperalgesia, improving the structure of articular cartilage, and reducing cartilage surface fibrillation ( B-Wang et al, 2020 ). Recently studies have shown that EA at ST36 excites the vagus nerve via its dorsal nucleus, activates the α7 nicotinic acetylcholine receptor (α7nAChR)-mediated Janus kinase 2/signal transducer and activator of transcription 3 (JAK2/STAT3) signaling pathway in macrophages, inhibits the expression of the inflammatory factors IL-6 and TNF-α, reduces the local immune responses in the gastrointestinal tract, and promotes the recovery of gastrointestinal motility in mice with postoperative intestinal paralysis ( Yang et al, 2021 ). These pieces of evidence suggest that macrophage polarization and the balance of related cytokines may be the main targets of acupuncture in its regulation of inflammatory pain.…”
Section: Acupuncture-induced Inhibition Of Peripheral Sensitivity In Inflammatory Pain Modelsmentioning
confidence: 99%
“…Recently, this group further demonstrated that EA at ST36 suppressed intestinal inflammation and promoted gastrointestinal motility. Mechanistically, EA activated the α7-nicotinic acetylcholine receptor (α7nAChR) -mediated JAK2/STAT3 signaling pathway in macrophages which reduced the production of inflammatory cytokines by acupuncture [ 55 ]. In addition, it has been also demonstrated that acupuncture at SP6 has an anti-inflammatory effect on peritonitis caused by carrageenan, resulting in decreased inflammatory cell infiltration and vascular permeability while increasing the levels of IL-10 [ 56 ].…”
Section: Macrophage Polarization In the Anti-inflammatory Action Of Acupuncturementioning
confidence: 99%